Increasing of Some Medical Flavonoid Compounds of Dodonaea viscosa L. using AgNO3 Nanoparticles In Vitro - Al-Aubaidi , Hashim K. M. (Iraqi Journal of Science, 2023)
The research was conducted to study the effect of adding different concentrations of AgNo3 Nanoparticles (0,0.5,1.0,1.5,2.0) mg/ l in the production of some secondary metabolic compounds(Quercetin, Luetolin and Apigenin) of plant Dodonaea viscosa L. Quantitative and qualitative analysis of secondary metabolites were estimated by using( HPLC ). The explants from leaves were culture on MS media supplemented with 2mg/l of 2,4-D, 0.5mg/l of NAA and 0.5 mg/l of BA for callus induction. Adding AgNo3 Nanoparticles (2 mg/l) cause in significant increase of Quercetin and Luetolin production, while adding AgNo3 Nanoparticles (0.5mg/l) led to significant increase of Apigenin in callus extract.